Perbandingan Luas Permukaan Telapak Tangan terhadap Luas Permukaan Tubuh berdasar Jenis Kelamin dan Indeks Massa Tubuh pada Dewasa Muda (Comparison of Hand Surface Area on Body Surface Area based on Sex and Body Mass Index in Young Adults ) - Fatmalia Fhierziandrini Nuzuliana; Ulfa Elfiah; Sheila Rachmania (Pustaka Kesehatan, 2018)
Hand surface area is considered as 1% of body surface area is used as one way in determining the extent of burns. There are differences of percentage of hand surface area in literatures. This study aimed to determine the ratio of hand surface area and palm surface area towards body surface area in young adults at the University of Jember based on Body Mass Index (BMI) and sex. This study was observational analytic with cross sectional approach. The samples were 120 young adults at the University of Jember, divided into 4 groups of BMI i.e. thin, normal, overweight, and obese. The analysis used in this study was One Way Anova and Independent T-test. The average percentage of the hand surface area on male 0.757%, female 0.702%, thin group 0.794%, normal 0.747%, overweight 0.704%, and obese 0.677%. Test analysis between men and women obtained significance value <0.05 while between groups of BMI obtained significance value <0.05 except between overweight and obese. It concluded that the percentage of hand surface area was different between genders and BMI groups. The percentage of the hand surface area was smaller with an increase of BMI. Keywords: hand surface area, body surface area, body mass index, sex